Analysis of Signature of Stainless Steel in Uzbekistan and Abroad - Kakharovich, Kasimov Umidjon; Karabaevna, Atakhanova Sayyora (Research Parks Publishers, 2022)
This article analyses the branding of stainless steels in Uzbekistan and abroad, the types of steels according to their use, chemical composition, type of application, hot and cold resistant stainless steel coils.